Teenage and Pre-Teenage Pregnancies in Vihiga County Kenya - Fozia, Nurwin; Asiko, Okanga Anne (International Journal of Humanity and Social Sciences, 2025)
Teenage pregnancies is a global public health concern more so in Vihiga county, the second smallest county in Kenya with the highest rural population in East and Central Africa with an average population of 1200 persons per square kilometer. In Kenya, in every four girls, one, between the ages of 15-19 becomes a mother. The purpose of this study was to identify the teen and preteen prevalence in Vihiga County. Simple random sampling was used to select the participants of the study. The findings found out that the preteen pregnancies rates are high and intervention is required for return to school and economic empowerment programmes. Policies relating to preteen pregnancies have to be reviewed to take into consideration the fact that majority of the affected never return to school. The practice Is they end up as dropouts and turn into child labour.